Pengaruh Brand Image Dan Persepsi Harga Terhadap Keputusan Pembelian Handphone Samsung (Studi Pada Masyarakat Kabupaten Pamekasan) - Dania Ulva; Nur Hidayati; Ita Athia (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of brand image and price perception on the purchase decision of the Pamekasan Regency Community. The type of research used is explanatory research with a quantitative approach. The sample in this study amounted to 120 respondents with the technique used in this study snowball sampling. The results showed that brand image and price perception had a positive effect on purchasing decisions. Brand image has a positive effect on purchasing. Price perception has a positive effect on purchasing. Keyword: Brand Image, price perception and purchasing decisions